2018
DOI: 10.1002/acr.23471
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hydroxychloroquine in Hand Osteoarthritis: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Treatment with HCQ at 24 weeks is not effective in reducing the symptoms of hand OA compared to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 27 publications
0
63
0
4
Order By: Relevance
“…However, the 2007 recommendations did not include advice on the use of these drugs, and no evidence was available at that time. Trials investigating the efficacy of hydroxychloroquine,53 69 70 different TNF-inhibitors71–74 and anti-interleukin-1,75 could not demonstrate efficacy of these antirheumatic drugs in patients with hand OA. Trials investigating methotrexate, sulfasalazine or colchicine have not been performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the 2007 recommendations did not include advice on the use of these drugs, and no evidence was available at that time. Trials investigating the efficacy of hydroxychloroquine,53 69 70 different TNF-inhibitors71–74 and anti-interleukin-1,75 could not demonstrate efficacy of these antirheumatic drugs in patients with hand OA. Trials investigating methotrexate, sulfasalazine or colchicine have not been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Retinoic acid is essential for forelimb development in the embryo and is a potentially interesting target as this metabolite has anti-inflammatory effects on many different cell types including chondrocytes 143 . Paradoxically, chondrocyte biologists use retinoic acid to stimulate cartilage catabolism (albeit at supra-physiological levels 144 .…”
Section: [H1] Disease Mechanismsmentioning
confidence: 99%
“…Evidence sug gests that hydroxychloroquine can delay or prevent organ damage 10 , including bone destruction 11 , in autoimmunity, and that this drug has antithrombotic effects 12 . Trials assessing antimalarial drugs in hand osteoarthritis, how ever, have found that hydroxychloroquine is no more effective than placebo in providing pain relief 13,14 , implying that although antimalarial drugs are useful for a selection of rheumatic diseases, they are not 'wonder drugs' .…”
mentioning
confidence: 99%